Sterane biomarker analysis of Sargelu Formation, Miran West Field, MW-2 well, Kurdistan Region, NE Iraq: Implications for origin of organic matter, palaeoenvironment and maturity - Salih, Danyar A.; Fatah, Sardar S.; Fatah, Sardar S.; Rashid, Fraidoon; Hakimi, Mohammed H.; Mohialdeen, Ibrahim M.J. (Sulaimani Journal for Pure and Applied Sciences, 2020)
Sargelu Formation (Middle Jurassic) is well known to be one of the most important and wide distributed source rocks in the Middle East. In this study, nineteen cuttings samples from Sargelu Formation were studied from one subsurface section within Miran West Field (well MW-2) in Zagros Folded Belt, Kurdistan region of Iraq. The Formation was penetrated from the interval 2375m to 2475m, which is mainly composed of argillaceous limestone and shale. The Total Organic Carbon (TOC wt %) for all samples were calculated from the sonic and resistivity logs using Passey et al., method for TOC estimation from wireline logs. The range of TOC percentage in the selected interval is between 0.654 and 6.53%. In addition, all samples have been analyzed by Gas Chromatography/ Mass Spectrometry (GC/MS) in order to identify and study the biomarkers distribution in the selected rocks. The short chain n-alkanes between C15-C18, with isoprenoids pristane (Pr) and phytane (Ph) are dominants in the Sargelu formation. The average of Pr/Ph ratio in the samples was 0.95. Furthermore, most of the studied samples show unimodal envelope chromatograms, maximum peak carbon n-C15- n-C20, and low CPI values (0.89-1.17). The calculated odd over even predominance (OEP) for the studied samples show near value 1.0 (av. 0.94). The TOC values reflecting well preservation and high productivity of organic matter in reducing/anoxic depositional environment. Moreover, ratios of Pr/Ph indicating to anoxic and commonly marine carbonate environments; and also unimodal envelope of n-C15- n-C20 shows a predominance of marine input, and the organisms derived from phytoplankton, zooplankton and benthic bacteria with minor photosynthetic and terrestrial plants. The studied samples have C29 20S/(20S+20R) and ββ/ (ββ+αα) isomerization values ranging from 0.39 - 0.58 and 0.48 - 0.65 respectively, indicating high mature source rocks of Sargelu Formation in this well. In most studied samples, the C27 and C29 steranes predominate over the C28 steranes, reflecting a high contribution of aquatic planktonic-bacterial organic matter with a minor terrigenous organic matter input.
Keywords: Sargelu Formation; Jurassic; Kurdistan; Biomarkers; Miran West Fiel; Hydrocarbons